1995
DOI: 10.1111/j.1524-4725.1995.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology of Vein Disease

Abstract: In evaluating the patient with leg symptoms the presence of specific symptoms increases the likelihood that vein disease is responsible independent of the size of the veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For example, the extent of the visible veins does not correlate with the severity or number of symptoms experienced (Goldman et al. , 1994; Isaacs, 1995). In addition, a complex interaction has been suggested between cosmetic dislike and perception of symptoms (Robbins et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the extent of the visible veins does not correlate with the severity or number of symptoms experienced (Goldman et al. , 1994; Isaacs, 1995). In addition, a complex interaction has been suggested between cosmetic dislike and perception of symptoms (Robbins et al.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between symptoms and presence of varicose veins has always been the subject of debate, with some authors finding that some symptoms attributed to varicose veins are found in patients with no evidence of venous disease (Bradbury et al. 1999; Isaacs 1995). Because of the difficulties in assessing certain symptoms, patients with mainly a cosmetic complaint might deny this symptom in order to obtain surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent varicose veins: Family history of varicose veins and a general history including pregnancies [19], and hormone therapy [19], deep vein thrombosis, obesity and a change of occupation should be recorded, related to varicose veins [20]. Aching legs, pain, heaviness fatigue, itching, burning, leg swelling (disappearing after leg rest), cramps, restless and throbbing legs [21] should be sought.…”
Section: Medical Historymentioning
confidence: 99%